Comparison of Pulsed-Gel Electrophoresis and a Commercial Repetitive-Element PCR Method for Assessment of Methicillin-Resistant Staphylococcus aureus Clustering in Different Health Care Facilities - Crnich, Christopher J.; Duster, Megan; Warrack, Simone; Maki, Dennis; Safdar, Nasia (Journal of clinical microbiology, 2014)
Pulsed-field gel electrophoresis (PFGE) is a common method used to type methicillin-resistant Staphylococcus aureus (MRSA) in nosocomial investigations and epidemiological studies but is time-consuming and methodologically challenging. We compared typing results obtained using a commercial repetitive-element PCR (rep-PCR) system with PFGE in a sample of 86 unique MRSA isolates recovered from subjects in an academic referral hospital and two nursing homes in the same geographic region. Both methods reliably assigned isolates to the same Centers for Disease Control and Prevention (CDC) pulsotype. PFGE was significantly more discriminatory (Simpson's index of diversity, 0.92 at the 95% strain similarity threshold) than the commercial rep-PCR system (Simpson's index of diversity, 0.58). The global (adjusted Rand coefficient, 0.10) and directional congruence (adjusted Wallace coefficient repPCR→PFGE = 0.06; adjusted Wallace coefficient PFGE→repPCR = 0.52) between the two methods was low. MRSA strains recovered from study nursing homes that were clonal when typed by the commercial rep-PCR method were frequently noted to be genetically distinct when typed using PFGE. These data suggest that the commercial rep-PCR has less utility than PFGE in small-scale epidemiological assessments of MRSA in health care settings.